RESPON PERTUMBUHAN TANAMAN DAN HASIL BEBERAPA VARIETAS PADI SAWAH TADAH HUJAN (Oryza sativa L.) AKIBAT PENERAPAN TEKNOLOGI - Ratnawati Ratnawati; Alfandi Alfandi; Iman Sungkawa (Program Studi Ilmu Pertanian Pascasarjana UGJ, 2019)
Rainfed land with an area of 1.4 million ha is the second rice barn after irrigation land for Indonesia. Understanding rainfed land is land that has a bund but cannot be irrigated with a certain height and time continuously. Therefore the irrigation of rainfed land is largely determined by rainfall so that the risk of drought often occurs in the area during the dry season. So far, rice varieties for rainfed land that have resistant properties to blast disease are still very limited. On the other hand, it is very necessary to diversify the resistant varieties of blast disease to overcome the disease so that the resistance genes are not easily broken. Therefore we need a number of varieties with a wide diversity of resistance genes that are recommended for planting by farmers. The Agricultural Research and Development Agency has released drought-tolerant rainfed lowland rice varieties and several pests and diseases such as Inpari 10, inpari 38, inpari 40, inpari 42, inpari 43 and HHZ5-DT1-DT1 lines. The research method used was Factorial RGD with the treatment of PTT application and conventional technology interacted with rice varieties.The results showed that the application of PTT technology had a real / good influence compared to conventional technology on the growth and yield of rice plants. PTT can increase production by 5.9% and income by 12.6%. Inpari 42, Inpari 43 and HHZ5-DT1-DT1 varieties are relatively more stable than other varieties and Inpari 43 has a higher production compared to other varieties.